Conformational isomerism in methyl cyanoacetate: A combined matrix-isolation infrared spectroscopy and molecular orbital study - Reva, Igor D. (2001)
Study of the conformational isomerism of methyl cyanoacetate (NCCH2COOCH3, MCA) aided for the first time by matrix-isolation infrared spectroscopy is reported. The conformational isomerization processes in MCA in the temperature range from 10 to 70 K were studied in detail in argon and xenon matrixes. During annealing of the matrixes direct interconversion of the gauche into the syn conformer has been registered. A similar, but more pronounced, gauchesyn interconversion effect was observed in a series of experiments in which matrixes were deposited at increased substrate temperature. The experiment is supported by theoretical predictions undertaken at different levels of approximation (MP2 and DFT/B3LYP). It is shown that, for the single molecule in vacuum, the syn conformer (C–C–CO dihedral angle equal to 0°) corresponds to the conformational ground state, with the doubly degenerated by symmetry gauche conformer (C–C–CO dihedral angle equal to ± 139.9°) being only slightly less stable than the most stable form (MP2/6-31G**E(gauchesyn)= 0.174 kJ mol–1). In the matrixes, the energy gap between the syn and gauche conformers increases, with E(gauchesyn) estimated to be about 1.4 kJ mol–1 in xenon. The predicted energy barriers for conformer interconversion were found to be significantly low: the MP2/6-31G** calculated E(syngauche) energy barrier is ca. 3.65 kJ mol–1, while the calculated energy barrier separating the two symmetrically equivalent gauche conformers stays only 0.196 kJ mol–1 above the energy of these forms. In the matrixes, E(syngauche) energy barrier increases to at least 17–18 kJ mol–1, while the E(gauchegauche) energy barrier is, with all probability, still lower than in the gaseous phase. The matrix isolation spectroscopic data indicate that interconversion between the gauche conformers occurs even in the low temperature matrixes.